1994
DOI: 10.1111/j.1525-1594.1994.tb02231.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility of Polytetrafluoroethylene Vascular Prostheses to Colonization by Staphylococcus aureus Following In Situ Endothelialization

Abstract: The impact of endothelialization of polytetrafluoroethylene (PTFE) grafts on susceptibility to experimental colonization by Staphylococcus aureus was studied in a rat model. One hundred and eight grafts (2 mm inner diameter, 5 mm length) were implanted into the infrarenal aorta (54 rats) or the infrarenal caval vein (54 rats). The progress of endothelialization following graft implantation was evaluated by SEM at 1, 3, 7, and 14 days on 6 grafts from each group. We found that the endothelialization was more ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…challenge with 10 8 S. aureus organisms 3 to 6 months after implantation, yielding infections in 10 to 80% of the animals, depending on the type of graft (17). Interestingly, a similar study with rats revealed that the infection rate of caval vein grafts was reduced from 100% to zero during 2 weeks of implantation as a result of increased endothelialization, while the infection rate of aorta grafts was still 100% after these 2 weeks (26).…”
Section: Discussionmentioning
confidence: 84%
“…challenge with 10 8 S. aureus organisms 3 to 6 months after implantation, yielding infections in 10 to 80% of the animals, depending on the type of graft (17). Interestingly, a similar study with rats revealed that the infection rate of caval vein grafts was reduced from 100% to zero during 2 weeks of implantation as a result of increased endothelialization, while the infection rate of aorta grafts was still 100% after these 2 weeks (26).…”
Section: Discussionmentioning
confidence: 84%